A biodegradable PEG-based micro-cavitary hydrogel as scaffold for cartilage tissue engineering. (November 2015) - Fan, Changjiang; Wang, Dong-An
Abstract : Graphical abstract: Highlights: The first preparation of biodegradable PEG-based micro-cavitary hydrogel (MCG). Micro-cavitary structure promotes diffusion, provides living space and accelerates degradation of MCG scaffolds. Biodegradable MCG scaffolds promote neo-cartilage formation. Abstract: We developed a micro-cavitary hydrogel (MCG) via photo-polymerization of biodegradable oligo(trimethylene carbonate)–poly(ethylene glycol)–oligo(trimethylene carbonate) diacrylate (TPT-DA) macromer, in which cavities with hundreds of microns in diameter were created using gelatin micro-spherical porogens. The capacity of this TPT-DA based MCG (TPT-MCG) as scaffolds for cartilage tissue engineering was deployed and measured by comparing it with conventional, non-cavitary TPT-DA based hydrogels (TPT-G). Besides the influence on physical properties (e.g. swelling behavior, crosslink density, etc.), the micro-cavitary structure properly accelerated degradation of TPT-MCG constructs, which benefited cell proliferation and production of cartilage-specific extracellular matrix (ECM). After 21 days of culture, the cell density in TPT-MCG constructs was 5.6-folds higher than that in TPT-G constructs. The total contents of collagen and glycosaminoglycan (GAG) in TPT-MCG constructs was up to 833 mg per gram dry weight in contrast with 273 mg per gram dry weight in TPT-G counterparts. Furthermore, the ECM networks were clearly observed in TPT-MCG constructs. These results indicate the superiority of TPT-MCG as scaffold for cartilage regeneration.